A corpus-based study on Chinese and American students' rhetorical moves and stance features in dissertation abstracts - Liu, Yingliang; Hu, Xuechen; Liu, Jiaying (Frontiers in Psychology, 2022)
While move structure and authorial stance in academic writing have received sufficient attention, studies have primarily concentrated on the whole text of journal articles. Dissertations is the most important research genre for graduate students as they step into the academic community. However, little is known about rhetorical move structure and interpersonal nature of academic communication in dissertation by L2 students. To address this issue, this study compares the use of stance markers and rhetorical moves in Chinese and American doctoral students’ English dissertation abstracts. Two corpora were constructed for the investigation: Corpus of Chinese Students’ Abstracts (CCSA) and Corpus of American Students’ Abstracts (CASA), each including 56 English dissertation abstracts in material science. Santos’ (1996) framework was employed to code the move structure of abstract in both corpora. Based on Biber’s (2006) classification, each type of stance markers was retrieved with the help of AntConc. The findings show that most of the abstracts in both corpora include the five moves of abstracts proposed by Santos (1996), namely, situating the research, presenting the research, describing the methodology, summarizing the findings, and discussing the research. However, fewer abstracts by Chinese students include all five moves. In addition, the choices of stance markers by the two groups vary across the five abstract moves for different communication purposes. Results of the study have pedagogical implications for facilitating development of academic writing skills for L2 writers.